Using guarding net to reduce regularly discarded invertebrates in trammel net fisheries operating on seagrass meadows (Posidonia oceanica) in Izmir Bay (Eastern Aegean Sea) - AYDIN, I.; GOKCE, G.; METIN, C. (Mediterranean Marine Science, 2013)
Prohibition of both beach and boat seines and trawl fishery along the İzmir Bay coasts in the Aegean Sea signifies intensive usage of gillnets and trammel nets, for catching red mullet (Mullus spp.) species in particular. Trials were realized between March 2009 and February 2010 with trammel nets in the areas on the boundaries of the sea grass (Posidonia oceanica) meadows in the Bay. Guarding net (selvedge) was attached to the lead line of experimental nets (Exp1-Exp2) - 36 and 40 mm inner panel. Differences for discard amounts between control group nets (C1-C2) (having the same inner panel as the experimental nets), used by commercial fishermen, and experimental nets are 54.7% for C1-Exp1 and 62.8% for C2-Exp2 (p<0.05). Use of nets with selvedge not only reduced regularly discarded invertebrates (Hexaplex trunculus, Bolinus brandaris, Maja spp.) in the region, but also avoided net damage caused by these species.